Comparative study of quasi steady and unsteady damping derivatives for delta wings in hypersonic flow for half sine wave - Renita, sharon Monis; Crasta, Asha; Khan, Sher Afghan; Parvathy, Rajendran; Erwin, Sulaeman (SEMARAK ILMU PUBLISHING, 2022)
Correlation investigation of quasi-steady and unsteady damping derivatives of delta wing is analyzed and contemplated, with leading edges bent in the current paper. The current paper realizes that the quasi-steady damping derivative considers only the rate of pitch, not the rate of the angle of attack. In contrast, unsteady damping derivatives account for pitch rate and the rate of the angle of attack. Results show a reformist reduction in the damping derivatives as the Mach number increases in quasi-steady and unsteady cases. Outcomes are computed for a varied range of Mach Numbers and deflection angles due to the pitch rate of different amplitudes of half-sine waves. The outcomes for the damping derivative for a fixed pivot position show different behavior for different values of the flow deflection angles observed here. As in straight leading edge, even in the curved leading edge, steady-state is attained earlier in quasi-steady than unsteady.